Gorilla [videorecording] - Jampel, Barbara; Kane, Dennis B.; Skinner, Thomas; National Geographic Society, Washington, D.C.; WQED (Television station : Pittsburgh, Pa.). ([Washington, D.C.] The Society, 1981)
Calls attention to the plight of the gorilla which is on the verge of extinction. Profiles a zookeeper, a research psychologist, a writer-photographer, and a husband and wife team working on the mountain gorilla project. Film footage demonstrates the animals intelligence, humanlike qualities, and the effects of their exploitation by humans.
VHS.
Narrated by E.G. Marshall ; Edited by Barry Nye ; Photography by K.K. Anmann/Bruce Coleman In, Ann Keiser.
Keywords: Gorilla; Apes; Monkeys; Rare animals; Wildlife conservation